Degradation Potential of Protocatechuate 3, 4-Dioxygenase from Crude Extract of Stenotrophomonas maltophilia Strain KB2 Immobilized in Calcium Alginate Hydrogels and on Glyoxyl Agarose. (12th February 2014) - Guzik, Urszula; Hupert-Kocurek, Katarzyna; Krysiak, Marta; Wojcieszyńska, Danuta
Abstract : Microbial intradiol dioxygenases have been shown to have a great potential for bioremediation; however, their structure is sensitive to various environmental and chemical agents. Immobilization techniques allow for the improvement of enzyme properties. This is the first report on use of glyoxyl agarose and calcium alginate as matrixes for the immobilization of protocatechuate 3, 4-dioxygenase. Multipoint attachment of the enzyme to the carrier caused maintenance of its initial activity during the 21 days. Immobilization of dioxygenase in calcium alginate or on glyoxyl agarose resulted in decrease in the optimum temperature by 5°C and 10°C, respectively. Entrapment of the enzyme in alginate gel shifted its optimum pH towards high-alkaline pH while immobilization of the enzyme on glyoxyl agarose did not influence pH profile of the enzyme. Protocatechuate 3, 4-dioygenase immobilized in calcium alginate showed increased activity towards 2, 5-dihydroxybenzoate, caffeic acid, 2, 3-dihydroxybenzoate, and 3, 5-dihydroxybenzoate. Slightly lower activity of the enzyme was observed after its immobilization on glyoxyl agarose. Entrapment of the enzyme in alginate gel protected it against chelators and aliphatic alcohols while its immobilization on glyoxyl agarose enhanced enzyme resistance to inactivation by metal ions.